STRATEGI PEMENUHAN HAK WARGA NEGARA UNTUK MENDAPATKAN SERTIFIKAT TANAH MELALUI PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) (STUDI DI DESA ROWOKELE KECAMATAN ROWOKELE KABUPATEN KEBUMEN) - Evi Nur Lia Sari; Erna Yuliandari; Rima Vien Permata Hartanto (Jurnal PPKn, 2019)
The purpose of this study is to find out: (1) Strategy to fulfill citizens 'rights to obtain land certificates through PTSL in Rowokele Village, Rowokele Subdistrict, Kebumen District and (2) Inhibiting factors and supporting the fulfillment of citizens' rights to obtain land certificates through PTSL in Rowokele Village Rowokele Subdistrict Kebumen District. The research method used is descriptive research method while the research approach used is a case study. The technique of taking research subjects used was purposive sampling and simple random sampling. Techniques of collecting data is use interviews, observation, and document analysis. To obtain of the data validity, this research uses data triangulation and methods triangulation, temporary data analysis techniques use interactive data analysis with the following stages: (1) collecting of data, (2) reduction of data, (3) data presentation, and (4) verification or conclusion. Based on the results of the study it can be concluded that : (1) the strategy to fulfill citizens 'rights to obtain land certificates through PTSL is achieved, with simple procedures and affordable costs so that citizens' rights are fulfilled (a) the right to recognition guarantee, protection, and legal certainty (b) The right to get facilities and special treatment and (c) To have own private property rights; (2) The inhibiting factor for fulfilling citizens' rights to obtain land certificates through PTSL in Rowokele Village consists of internal constraints which include: difficulties in finding a history of land ownership and multiple land data. While external constraints include: community factors that do not understand the function and usefulness of land certificates, the geographical conditions of the Rowokele Village area and land certificates that have not been submitted. Meanwhile the supporting factors for fulfilling citizens' rights to obtain land certificates through PTSL in Rowokele Village are support from various parties and community participation, collaboration and coordination of committees.   Full Paper